2022
DOI: 10.3390/en15093291
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Induction Machines

Abstract: Induction machines are one of the most important technical applications for both the industrial world and private use [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The mouth depth, h 11 , was considered as 1.3 times the slot tip depth (h 11 = h 10 × 1.3 = 0.0009 m). As per [9], the mouth depth was between 1 and 1.5 times the slot tip depth.…”
Section: Design Of Single-phase Induction Motormentioning
confidence: 95%
See 1 more Smart Citation
“…The mouth depth, h 11 , was considered as 1.3 times the slot tip depth (h 11 = h 10 × 1.3 = 0.0009 m). As per [9], the mouth depth was between 1 and 1.5 times the slot tip depth.…”
Section: Design Of Single-phase Induction Motormentioning
confidence: 95%
“…It has also been observed that most high-power applications of electric motors, such as high-performance cars (e.g., Tesla and Porsche) employ fluid-cooled electric motors It has also been observed that most high-power applications of electric motors, such as high-performance cars (e.g., Tesla and Porsche) employ fluid-cooled electric motors for better cooling efficiency compared to fan cooling, which also takes up space and can lead to overheating. Electric motors are used for various applications ranging from industrial to domestic applications, and induction motors (rotating or linear) are the most used units [7][8][9][10][11]. Water-cooling systems might suffer from leakage issues if not properly designed and maintained.…”
Section: Introductionmentioning
confidence: 99%
“…The papers presented in this Special Issue cover a wide range of selected problems of advances in electric traction systems [1][2][3][4][5][6][7][8], electric drives for ground and air transport [9][10][11], DC [12,13] and AC [14,15] power supply used in network traction, automation and control [16,17], and energy savings that help the environment [18].…”
Section: Overview Of Contributions To This Special Issuementioning
confidence: 99%
“…Modern electric traction vehicles are complex engineering systems equipped with high-end solutions in electromechanics, electronics, automation and IT, especially in high-speed railways which have achieved record speeds of up to 574 km/h in France (AGV in 2008), with trains in China travelling at 380 km/h in regular service. The application of AC motors makes it possible to apply electric braking more effectively [5,6].…”
Section: Introductionmentioning
confidence: 99%